Electrical power generation in aircraft: review, challenges and opportunities - Madonna, Vincenzo; Giangrande, Paolo; Galea, Michael (Institute of Electrical and Electronics Engineers, 2018)
The constant growth of air traffic, the demand for performance optimization and the need for decreasing both operating and maintenance costs have encouraged the aircraft industry to move towards more electric solutions. As a result of this trend, electric power required on board of aircraft has significantly increased through the years, causing major changes in electric power system architectures. Considering this scenario, the paper gives a review about the evolution of electric power generation systems in aircraft. The major achievements are highlighted and the rationale behind some significant developments discussed. After a brief historical overview of the early DC generators (both wind- and engine-driven), the reasons which brought the definitive passage to the AC generation, for larger aircraft, are presented and explained. Several AC generation systems are investigated with particular attention being focused on the voltage levels and the generator technology. Further, examples of commercial aircraft implementing AC generation systems are provided. Finally, the trends towards modern generation systems are also considered giving prominence to their challenges and feasibility.